Upper Homerian (Silurian) high-resolution correlation using cyclostratigraphy: an example from western Lithuania - Radzevičius, Sigitas; Tumakovaitė, Brigita; Spiridonov, Andrej (Acta Geologica Polonica, 2017)
The Gėluva regional stage stratigraphically corresponds to the late Wenlock. This time interval witnessed significant graptolite extinctions and turnovers of conodont faunas, as well as a large positive Mulde carbon isotopic excursion. Thus, the development of a detailed stratigraphy is a necessary step in understanding the complex patterns of regional and global variations in the sediments accumulating during the time interval studied. Therefore, in this contribution we present a cyclostratigraphic analysis of gamma ray (GR) logs from four wells, which are located in the deep water facies belt of the Lithuanian part of the Silurian Baltic Basin of the Gėluva regional stage. The analysis was performed using REDFIT spectral estimation, continuous wavelet transform and signal filtering techniques. As a result two 4th order and five 5th order cycles were distinguished and named in all sections. The correlation of cycles between sections was calibrated with the graptolite biozones. The comparative analysis revealed that intra-basinal cyclostratigraphic correlation could achieve resolution of the order of several tens of thousands of years.
Keywords: Lithuania; Silurian; Upper Homerian; Cyclostratigraphy; Graptolite biozones